2022
DOI: 10.4103/ijnmr.ijnmr_84_21
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experiences of Iranian Patients with Rheumatoid Arthritis

Abstract: Background: Rheumatoid Arthritis (RA) is a chronic inflammatory disease that affects various systems of the body. The present study was conducted with the aim to explain the lived experiences of Iranian patients with RA. Materials and Methods: According to the research question, the phenomenological research approach was used. The participants were selected through purposive sampling, and sampling was continued until data saturation was achieved. The data was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Another qualitative study showed that the feeling of being close to death is one of the most essential negative experiences of patients affected by COVID‐19. The participants declared that announcements of deaths on social media made them concerned regarding the incurability of the disease (Ardakani et al., 2022 ). Several tragic deaths might accompany life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another qualitative study showed that the feeling of being close to death is one of the most essential negative experiences of patients affected by COVID‐19. The participants declared that announcements of deaths on social media made them concerned regarding the incurability of the disease (Ardakani et al., 2022 ). Several tragic deaths might accompany life.…”
Section: Discussionmentioning
confidence: 99%
“…The literature review showed various studies were performed regarding the experience of COVID‐19 patients (Ardakani et al., 2022 ; Firouzkouhi et al., 2023 ; Realino et al., 2023 ; Sahoo et al., 2020 ). In this regard, a qualitative study in Iran showed that patients declared that during the disease, they experienced incredible clinical symptoms, fear of stigma, and bad memories of hospitalization (Firouzkouhi et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The personal feelings of COVID-19 patients under mechanical ventilation affect their reactions and their ability to reach a previous stable state. Thus, an awareness of the patient's experiences and feelings can open a window toward a better understanding of the expectations of COVID-19 patients admitted to the ICU [15].…”
Section: Introductionmentioning
confidence: 99%